Limitations in Total Laparoscopic Hysterectomy in Bangladesh - Ila, Israt Jahan; Ghani, Afroza; Ferdouse, Jannat Ara; Khatun, Asia; Rahman, Sumana; Hasan, Jobayed; Hassan, Mohammad Rashedul (Journal of Shaheed Suhrawardy Medical College, 2018)
Laparoscopic Hysterectomy is achieving great popularity nowadays. Our people are becoming increasingly interested in new advances in this field of surgery. Highly skilled surgical technique, longer operative time and expensive technology are observed to be the factors that impede the advancements in laparoscopic surgery1. Objective: The aim of our study is to analyze the limitations of laparoscopic hysterectomy in our country. Methods: This is a retrospective observational study where we have reviewed demographic data, compliance of the patients, quality of anaesthesia, efficiency of supportive staffs, adequacy of appropriate instruments, continuous training of surgeons and surgical risk factors. Total 80 Total Laparoscopic Hysterectomy (TLH) were done between January’ 2016 to December’2017 in Shaheed Suhrawardy Medical College Hospital (ShSMCH), Dhaka. Result: In this study, we analyzed eighty patients who underwent total laparoscopic hysterectomy for fibroid uterus, adenomyosis, recurrent post-menopausal bleeding, abnormal Uterine bleeding(AUB) etc. We tried to analyze some limitations and challenges which we can overcome. In spite of lack of appropriate instruments, adequate ICU support and repeated training in specialized centre at home and abroad, 87.5% patients recovered well. The aim of our study was to identify the surgical risk factors of the patients and limitations in our theatre environment J Shaheed Suhrawardy Med Coll, June 2018, Vol.10(1); 3-5